Increased L-[1-(11)C]leucine uptake in the leptomeningeal angioma of Sturge-Weber syndrome: a PET study - Alkonyi, Bálint (2011)
BACKGROUND AND PURPOSE: We used L-[1-(11)C]leucine (LEU) positron emission tomography (PET) to measure amino acid uptake in children with Sturge-Weber syndrome (SWS), and to relate amino acid uptake measures with glucose metabolism. METHODS: LEU and 2-deoxy-2[(18)F]fluoro-D-glucose (FDG) PET were performed in 7 children (age: 5 months-13 years) with unilateral SWS. Asymmetries of LEU uptake in the posterior brain region, underlying the angioma, and in frontal cortex, were measured and correlated with glucose hypometabolism. Kinetic analysis of LEU uptake was performed in 4 patients. RESULTS: Increased LEU standard uptake value (SUV, mean: 15.1 %) was found in the angioma region in 6 patients, and smaller increases in LEU SUV (11.5 %) were seen in frontal cortex in four of the 6 patients, despite normal glucose metabolism in frontal regions. High LEU SUV was due to both increased tracer transport (3/4 patients) and high protein synthesis rates (2/4). FDG SUV asymmetries in the angioma region were inversely related to LEU SUV asymmetries (r=−0.83, p=0.042). CONCLUSIONS: Increased amino acid uptake in the angioma region and also in less affected frontal regions may provide a marker of pathological mechanisms contributing to chronic brain damage in children with SWS.